An empirical application of "broken windows" and related theories in healthcare: examining disorder, patient safety, staff outcomes, and collective efficacy in hospitals - Louise A. Ellis; Kate Churruca; Yvonne Tran; Janet C. Long; Chiara Pomare; Jeffrey Braithwaite (BMC, 2020)
Abstract Background Broken windows theory (BWT) proposes that visible signs of crime, disorder and anti-social behaviour - however minor - lead to further levels of crime, disorder and anti-social behaviour. While we acknowledge divisive and controversial policy developments that were based on BWT, theories of neighbourhood disorder have recently been proposed to have utility in healthcare, emphasising the potential negative effects of disorder on staff and patients, as well as the potential role of collective efficacy in mediating its effects. The aim of this study was to empirically examine the relationship between disorder, collective efficacy and outcome measures in hospital settings. We additionally sought to develop and validate a survey instrument for assessing BWT in hospital settings. Methods Cross-sectional survey of clinical and non-clinical staff from four major hospitals in Australia. The survey included the Disorder and Collective Efficacy Survey (DaCEs) (developed for the present study) and outcome measures: job satisfaction, burnout, and patient safety. Construct validity was evaluated by confirmatory factor analysis (CFA) and reliability was assessed by internal consistency. Structural equation modelling (SEM) was used to test a hypothesised model between disorder and patient safety and staff outcomes. Results The present study found that both social and physical disorder were positively related to burnout, and negatively related to job satisfaction and patient safety. Further, we found support for the hypothesis that the relationship from social disorder to outcomes (burnout, job satisfaction, patient safety) was mediated by collective efficacy (social cohesion, willingness to intervene). Conclusions As one of the first studies to empirically test theories of neighbourhood disorder in healthcare, we found that a positive, orderly, productive culture is likely to lead to wellbeing for staff and the delivery of safer care for patients.